Influencia de la participación familiar en el rendimiento académico de los estudiantes de la escuela John F. Kennedy del cantón La Maná en el periodo lectivo 2012 -2013 - Álava García, Jessenia Belén (2015)
This investigation determined the influence of family involvement in the academic performance of students of the School “JOHN F. KENNEDY” during the academic year 2012 - 2013, to gather the information was necessary to use the technique of the survey of teachers and students of the institution, through research we can conclude that there is active participation of parents in education of students, this factor makes the processes and integration that absent there is a lack of motivation, this research was conducted with the aim of contributing to accurate information about the problems teachers to benefit students, and the process of awareness to parents about the negative influences that the lack of them can generate in the educational progress of children jeopardizing the proper functioning of the educational process, for it was a methodological guide that allows the strengthening of family involvement to influence the development of children Campus